Sodium nitrate (NaNO3) sensor based on graphene coated microfiber - Yasin, Moh; Irawati, Ninik; Harun, Sulaiman Wadi; Ahmad, Fauzan; Khasanah, Miratul (Elsevier, 2019)
We demonstrate the coating of graphene onto the silica optical microfiber sensor for improving sodium nitrate detection at room temperature. The graphene obtained from graphene- polylactic acid filament was coated onto the microfiber based on drop casting technique. In the proposed sensor, the graphene acts as cladding to interact with analyte as well as functions to trap either sodium cation or nitrate anion and increases the effective refractive index of the cladding. The proposed sensor shows a good sensitivity of 1.29 dBm/% and resolution of 0.049%. The sensitivity, repeatababilty and reversible response of the sensor were improved by the coating of graphene layer. The presence of graphene on the surface microfiber works as passive cladding and influence the light propagation through the microfiber. © 2019 Elsevier Ltd